AN EXAMINATION OF SENSE OF CLASSROOM COMMUNITY AND LEARNING AMONG AFRICAN AMERICAN AND CAUCASIAN GRADUATE STUDENTS - Rovai, Alfred P.; Ponton, Michael K. (Online Learning, 2005)
Higher education administrators and faculty members seek ways in which to advance student learning in online courses, and student affairs professionals seek ways to promote a sense of belonging and connectedness of students to their schools. The present study examined how a set of three classroom community variables were related to a set of two student learning variables in a predominantly White sample of 108 online African American and Caucasian graduate students. Using canonical correlation, the two subscales of the Classroom Community Scale and the mean number of messages posted each week to the online course’s group discussion boards were found to be related significantly to perceived learning and total points earned in the course along a single dimension. Moreover, African American students scored significantly lower across all five variables than their Caucasian peers, suggesting that the achievement gap that exists in many traditional educational programs also exists in graduate ALN programs and that this gap extends to sense of community.